From Fandom to Frontline: Indonesian K-Popers, Islamic-Pop Activism, and Digital Solidarity for Palestine - Ni'am, Mohammad Fattahun (Jurnal Sosiologi Reflektif, 2025)
The recent resurgence of pro-Palestinian activism among Indonesian youth reflects not only growing humanitarian concern but also the evolving role of digital communities in political discourse. Within this landscape, K-pop fandoms—once seen as apolitical entertainment spaces—have emerged as unexpected yet powerful platforms for solidarity movements. This research aims to examine how Indonesian K-Popers, particularly the Xkwavers community, construct digital solidarity networks for Palestine. This study employs a qualitative case study approach, utilizing digital data collection techniques through Xkwavers’ online content, virtual participant observation, and in-depth interviews with community members. Data were analyzed using thematic coding, guided by Manuel Castells’ theory of the network society, specifically his four dimensions of power. The findings reveal that Xkwavers operates not only as a fandom collective but also as a religio-cultural movement that mobilizes donations, performs BDS campaigns, and shapes pro-Palestinian narratives through Islamic-pop aesthetics. Symbolic figures such as Fuad Naim serve as authoritative nodes who legitimize religious and political messages, amplified further by algorithmic logics of social media platforms. The study shows that K-pop-based activism is neither spontaneous nor purely cultural; rather, it is the outcome of complex power configurations within digitally mediated networks. The implication of this research is the need to recognize fandom-based digital communities as emerging sociopolitical actors in shaping transnational solidarity and public discourse in the digital age. Meningkatnya kembali aksi dukungan terhadap Palestina di kalangan anak muda Indonesia tidak hanya menunjukkan kepedulian kemanusiaan, tetapi juga peran baru komunitas digital dalam wacana politik. Di tengah fenomena ini, fandom K-pop—yang sebelumnya dianggap sekadar ruang hiburan apolitis—berubah menjadi wadah solidaritas yang aktif dan berpengaruh. Penelitian ini bertujuan untuk mengkaji bagaimana K-Popers Indonesia, khususnya komunitas Xkwavers, membangun jaringan solidaritas digital untuk Palestina. Penelitian ini menggunakan pendekatan kualitatif berupa studi kasus dengan teknik pengumpulan data secara digital pada konten-konten Xkwavers, observasi virtual partisipatif, dan dilengkapi dengan wawancara mendalam terhadap anggota komunitas. Data dianalisis menggunakan teknik pengodean tematik dengan kerangka teori masyarakat jaringan dari Manuel Castells, khususnya empat bentuk kekuasaan dalam jaringan. Hasil penelitian menunjukkan bahwa Xkwavers tidak hanya berperan sebagai komunitas penggemar, tetapi juga sebagai gerakan budaya-religius yang menggalang donasi, melakukan kampanye BDS, dan membangun narasi pro-Palestina melalui estetika Islam-pop. Figur seperti Fuad Naim menjadi simpul otoritatif yang memberi legitimasi religius dan politik, diperkuat oleh algoritma media sosial. Penelitian ini menunjukkan bahwa aktivisme berbasis K-pop bukanlah gerakan spontan atau murni budaya, melainkan hasil dari konfigurasi kuasa yang kompleks dalam jaringan digital. Implikasi dari penelitian ini adalah pentingnya mengakui komunitas digital berbasis fandom sebagai aktor sosial-politik baru dalam membentuk solidaritas lintas negara dan wacana publik di era digital.